THE INFLUENCE OF BILINGUALISM ON THE COGNITIVE DEVELOPMENT OF CLASS I STUDENTS AT SDN SUKASENANG - Silmi Ahsanti Dewi; Siti Sopiah; Ichsan Fauzi Rachman (Media Inovasi Pendidikan dan Publikasi, 2024)
This study addresses the effect of bilingualism on cognitive development in individuals with dual language abilities. This research explores how dual language skills influence various aspects of cognitive processes, such as problem solving, creativity, flexibility of thinking, and decision making. The research method used involves a literature review of relevant previous studies as well as analysis of empirical data from case studies and field experiments that have been carried out. Results showed that bilingualism has a significant impact on individuals' cognitive development. The ability to switch between two or more languages results in brain exercises that can increase cognitive flexibility and optimize executive functions, such as impulse control and problem solving. Additionally, bilingualism is also associated with higher cognitive abilities in certain domains, such as memory, attention, and information processing. This research contributes to our understanding of the importance of bilingualism in the cognitive development of individuals and its implications in the context of education and cognitive interventions. These findings provide a strong foundation for efforts to encourage the development of dual language skills at the level of individuals and society at large in order to improve cognitive quality and develop overall human potential.